Recipes and Songs : An Analysis of Cultural Practices from South Asia - Parveen, Razia (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book presents a systematic approach to the literary analysis of cultural practices. Based on a postcolonial framework of diaspora, the book utilizes literary theory to investigate cultural phenomena such as food preparation and song. Razia Parveen explores various diverse themes, including the female voice, genealogy, space, time, and diaspora, and applies them to the analysis of community identity. This volume also demonstrates how a literary analysis of oral texts helps to provide insight into women's lived narratives. For example, Parveen discusses how the notion of the 'third space' creates a distinctly feminine spatiality. .
Keywords: Social sciences.; Ethnology -- Asia.; Ethnology -- Europe.; Ethnology.; Sociology.; Religion and culture.; Sex (Psychology).; Gender expression.; Gender identity.; elektronické knihy; electronic books